Christian prophecy the post-biblical tradition - Hvidt, Niels Christian (Oxford ; New York : Oxford University Press, 2007)
Niels Christian Hvidt argues that prophecy has persisted in Christianity as an inherent and continuous feature in the life of the church. He presents a comprehensive history of prophecy from ancient Israel onwards and closely examines the development of theological discourse about it.
Introduction -- Prophecy and theology -- Prophecy and history -- Prophecy and revelation -- Prophecy and the end of revelation -- Prophecy and tradition -- Prophecy and sociology of religion -- Prophecy's status and types of faith -- Prophecy and truth.
Includes bibliographical references (p. [375]-400) and index.
Description based on print version record.
Keywords: Prophecy -- Christianity; RELIGION -- Christian Theology -- General; Electronic books